FENG SHUI PADA TATA LETAK MASSA BANGUNAN DI KELENTENG SAM POO KONG - Marcella, Benedicta Sophie (Universitas Atma Jaya Yogyakarta, 2012)
Abstract: â€œKlentengâ€ is an Indonesian term for place of worship for Chinese traditional faiths in Indonesia. Sam Poo Kong temple is a heritage building located in Semarang. Chinese temple building is part of the China building architecture, thus Chinese temple apply the feng shui principals, so that people get the fortune, peace, and prosperity from the perfect balance with nature. In this research, to be conducted a review of the use of feng shui principles contained in the layout of the building mass. The research question that arises is